High-density polyethylene composite filled with red mud: effect of coupling agent on mechanical and thermal properties. Issue 21 (19th September 2022) - Ding, Chong; Zhang, Youpeng; Di, Xiangyun; Zhang, Na; Zhang, Yihe; Wang, Xinke
ABSTRACT: In this study, red mud (RM) was modified with titanate coupling agent (triisostearoyl isopropoxy titanate, KR-TTS), and then the modified RM was melted blending with high-density polyethylene (HDPE) to prepare HDPE-based composite. The action mechanism of KR-TTS on the properties of HDPE composites was analysed combining with the movement mode of polyethylene macromolecular chain segments. The entanglement and mechanical interlocking of long alkyl chains of titanate coupling agent and the polyethylene molecular chains occurs in modified RM/HDPE composite, reflected by fracture morphology within tension process. The stronger interface interaction results in a decrease of polyethylene molecular chain segments motion under external loading, externally expressed as higher tensile strength and tensile modulus as well as storage modulus. Meanwhile, KR-TTS imparts modified RM/HDPE composite with higher elongation at break of uniaxial tension and lower damping ratio. The impact strength presents an improvement from 5.62 kJ/m 2 of RM/HDPE composite to 6.56 kJ/m 2 of modified RM/HDPE composite due to stronger interface strength. And modified RM/HDPE composite appears higher thermal stability, attributed to better particles dispersion and higher interface adhesion. Differential scanning calorimetric analysis shows that with the addition of coupling agent, the melt enthalpy of modified RM/HDPE composite decreases, indicating a decrement in the crystallinity of polyethylene composites (from 70.2% of RM/HDPE to 63.1% of modified RM/HDPE), resulted from the retarded stacking speed of chain segments into the crystal lattice during crystal growth. GRAPHICAL ABSTRACT: UF0001